Effectiveness of School Library Services at SMK Negeri 1 Soppeng - Muh. Nasrullah; Nurul Wahdaniah; Jamaluddin Jamaluddin; M. Said Zainuddin (Pinisi Journal of Education and Management, 2023)
Libraries have a very important role for the world of education. The library is not only used as a place to place books, but the library can be used as a place to learn and get sources of information. One of the types of libraries that exist is the school library. This study aims to determine the effectiveness of school library services at SMK Negeri 1 Soppeng. This research is a quantitative research with a descriptive research type. The sample in this study was 81 people using simple random sampling technique. Data collection techniques used are observation, questionnaires, and documentation. The results of the study show that library services at SMK Negeri 1 Soppeng are in the effective category. This research shows that the importance of library services and librarian services in serving the needs of users so that users can feel satisfied with the quality of services provided.